The effect of chemotherapy in patients with stage I mucinous ovarian cancer undergoing fertility-sparing surgery - Long, Xingtao; Li, Rengui; Tang, Ying; Yang, Lingling; Zou, Dongling (Frontiers in Oncology, 2022)
Objective: To determine the effect of adjuvant chemotherapy in patients with stage I mucinous ovarian cancer (MOC) undergoing fertility preserving surgery. Patients and Methods: The clinicopathological characteristics and survival information of young women with stage I MOC from SEER databases between 2004 and 2019 were collected. The relationship between chemotherapy and the characteristics was examined by univariate and multivariate logistic regression analyses. Univariable and multivariate Cox proportional hazards survival analysis were employed for 10-year cancer-specific survival. Cox analysis was performed to build a nomogram model. Results: All 901 eligible patients with stage I MOC were screened from the SEER database. There were 321(35.6%) patients aged 9-30, 580(64.4%) aged 31-45, 645 (71.6%) patients with stage IA/IB, 256 (28.4%) with stage IC disease, 411(45.6%) underwent uterine-sparing surgery, 276(30.6%) received postoperative adjuvant chemotherapy. Multivariate logistic regression analyses showed that postoperative chemotherapy was often used in patients aged 31-45 relative to aged 9-30 (HR: 2.215,95%CI 1.443-3.401, P < 0.001) or with poorly-differentiated compared to well-differentiated tumors (HR: 7.382, 95%CI 4.054-13.443, P < 0.001) or with stage IC compared to stage IA/IB (HR: 6.436,95%CI 4.515-9.175, P < 0.001) or with non-uterine sparing surgery relative to uterine-sparing (HR:2.226, 95%CI 1.490-3.327, P < 0.001). Multivariate analysis indicated that patients with chemotherapy (HR: 2.905, 95% CI: 1.059-7.972, P=0.038) or with grade 3 (HR: 4.677, 95% CI: 1.356-16.130, P=0.015) had a greater risk of mortality. A prognostic prediction nomogram model was built for stage I MOC patient underwent fertility-sparing and the C-index was 0.709. Discussion: The patients aged 31-45, with poorly differentiated, IC stage, and none-fertility sparing surgery were more likely to receive adjuvant chemotherapy in real world. For stage I MOC patient underwent fertility-sparing surgery, the choice of chemotherapy may increase the risk of death, and it should be carefully selected in clinical practice.